Composição da cera cuticular e qualidade de maçãs ‘Royal Gala’ submetidas à aplicação pós-colheita de vapor de etanol - Cagliari, Franciele (2023)
Apples are one of the most widely grown and consumed fruits in the world, and the entire volume produced is not used immediately. Therefore, efficient storage is needed to preserve product quality and reduce losses. Controlled atmosphere (CA) storage is widely used, along with ethylene action inhibitors such as 1-MCP, to guarantee product quality. Other techniques are being researched, such as the use of ethanol, a natural compound that has been gaining interest as an alternative to 1-MCP, as it is a simple, low-cost technique with few negative effects. One of the most important aspects is the study of the tissue that covers plants, since this surface provides the interface between the fruit and the environment. In addition, the process by which consumers decide to buy involves sensory aspects, and good acceptance is related to the visual characteristics presented by the peel. The cuticle affects the post-harvest quality of apples, highlighting its composition and changes during storage. However, the impact of ethanol vapor on the biochemistry of the cuticle is still little explored, which motivates the investigation of its effects in order to better understand its role in the quality and shelf life of apples exposed at room temperature. The aim of this study was to evaluate the quality and cuticular wax components of 'Royal Gala' apples subjected to different doses of ethanol vapor during their exposure to room temperature for 14 days, simulating extended shelf life. The experiment was conducted in a completely randomized design. The treatments combined the application of different doses of ethanol vapor, including the control (1) were: (2) 200 μL L-1; (3) 400 μL L-1; (4) 600 μL L-1; and (5) 1000 μL L-1. Ethanol vapor had no influence on respiration parameters, however, ethylene production was reduced by doses of 200 μL L-1 to 600 μL-1 up to the 4th day of shelf life. The ethanol vapor dose of 400 μL L-1 provided 'Royal Gala' apples with greater maintenance of pulp firmness, a reduction in the occurrence of pulp degeneration and the incidence of rot. On the other hand, the highest dose of ethanol vapor resulted in lower ACC oxidase activity and higher internal ethanol content. The cuticular wax content of the apples does not seem to have been affected by the ethanol vapor treatment, however, it requires further investigation. Of the 39 wax components identified, the dose of 400 μL L-1 of ethanol vapor was the most efficient in maintaining the quantity of fatty acids. There was no significant impact of ethanol vapor treatment on the other compounds.